High-throughput real-time PCR and melt curve analysis for sexing Southern Ocean seabirds using fecal samples - Faux, C.; McInnes, J.; Jarman, Simon (2014)
Sex identification of birds is of great interest in ecological studies, however this can be very difficult in many species because their external features are almost monomorphic between the sexes. Molecular methodology has simplified this process but limitations still occur with widely accepted methods using polymerase chain reaction and gel electrophoresis, especially when applied to degraded DNA. Real-time polymerase chain reaction assays are emerging as a more efficient, sensitive, and higher throughput means of identification, but there are very few techniques validated using fecal samples and small target sizes. We present a real-time melt curve analysis assay targeting a small region of the CHD-1 gene allowing for high-throughput, sensitive, specific, and easy-to-interpret sexing results for a variety of Southern Ocean seabirds using fecal and tissue samples. © 2014 The Authors.